Designing M â€“ RIES (Mental Retardationâ€™s English Vocabularies) As Learning Media For Mild Mental Retardation Students - Septian Ragil Anandita; Abadi Kharisa Putri Z; Iin Baroroh Maarif; Luluk Choirun Nisak Nur (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2024)
English is a part of the curriculum in Indonesian schools and universities, even English is used as the extra lessons and programs developed in inclusive schools or local content specifically provided as the studentâ€™s knowledge of the language. The objective of the research is to designing M â€“ RIES (Mental Retardation English Vocabularies) as learning media for mild mental retardation students. The researcher used Research and Development (R&D) methods. In this research procedure adapts ADDIE model that consist of five stages. Those are: analysis, design, development, implementation, and evaluation. The researcher used observation and questionnaire to collect the data. This media has been validated by 4 experts before being implemented to the students. The result of the material experts validator obtained 82,5% and 90% in the â€œStrongly Agreeâ€ category. In addition, the result of media experts validator obtained 89,4% and 96,4% that was also include in â€œStrongly Agreeâ€ category. The researcher conducted trials on 4 mild mental retardation students at SMALB Tunas Harapan 1 Tembelang. The result of implementation obtained 95% were in â€œVery Goodâ€ category. By having those results, this M â€“ RIES media is feasible to be used as learning media for mild mental retardation students. Key words:Â Learning Media, Mild Mental Retardation, M â€“ RIES, R&D, Vocabularies Â